Mechanical properties of methyl functionalized single-walled carbon nanotube - Goh, Ivan Peck Chen. (2011)
Molecular dynamics simulations have been conducted to investigate the effect of methyl (CH3) functionalization on the mechanical properties of single-walled carbon nanotubes (SWCNT). Small numbers of CH3 radicals were chemically absorbed on SWCNT in two ways: axially and circumferentially.